Factors influencing farmers' adoption and willingness to accept sustainable production practices in Istria County, Croatia - Melita ZEC VOJINOVIĆ; Ana Čehić Marić; Milan Oplanić (Journal of Central European Agriculture, 2025)
To ensure food security and mitigate environmental degradation caused by conventional farming, the adoption of sustainable production systems or practices is essential. Despite the availability of diverse sustainable agricultural practices, their widespread adoption remains limited. Thus, this study aimed to assess the importance of socioeconomic and socio-demographic characteristics of farmers, as well as farm characteristics, on their interest in transitioning to Sustainable Production Systems (SPS) or adopting Sustainable Agricultural Practices (SAP). Additionally, the study evaluated the motivational factors affecting farmers' WTA for some of the SPS or SAP in Istria County, Croatia. A survey was conducted on 172 farms in Istria County. The data were analysed using descriptive statistics, ANOVA to identify statistical differences, and chi-square tests to determine associations between variables. The results indicate that nearly half of the respondents were interested in transitioning to SAS or adopting SAP. Higher education levels significantly correlate with a greater interest in adopting SAS or SAP. When farmers were offered benefits such as financial support during the trial period, sales assistance, and product marketing, the WTA was significantly higher. Applying Rogers' Diffusion of Innovations (DOI) theory, the study highlights the importance of perceived relative advantage, compatibility, and trialability in adoption decisions. Despite the several limitations of this study, the findings underscore the need for integrated approaches combining education, financial incentives, and technical support to achieve widespread adoption of sustainable agriculture.